The voyage of John Huyghen van Linschoten to the East Indies : from the old English translation of 1598, the first book, containing his description of the East. Volume I - Linschoten, Jan Huygen van, 1563-1611 (Ashgate, 2010)
The English translation is that of William Phillip. For the second volume, see First Series 71. The supplementary material consists of the 1884 annual report. First published: 1885.